2016
DOI: 10.1103/physrevc.94.024616
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of transfer coupling in sub-barrier fusion ofTi46,50+Sn124

Abstract: Background The presence of neutron transfer channels with positive Q-values can enhance sub-barrier fusion cross sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…One explanation is that the dynamics will "wash out" the static structure effects such as the Coulomb barrier lowering due to neutron skin [30]. This anomaly was also studied in a recent experiment [31].In this work we address the impact of isospin dynamics on fusion barriers and cross-sections using the microscopic timedependent Hartree-Fock (TDHF) theory [32,33] together with the density-constrained TDHF (DC-TDHF) method for calculating fusion barriers [34]. In the TDHF approximation the many-body wavefunction is replaced by a single Slater determinant and this form is preserved at all times, implying that two-body correlations are neglected.…”
mentioning
confidence: 83%
“…One explanation is that the dynamics will "wash out" the static structure effects such as the Coulomb barrier lowering due to neutron skin [30]. This anomaly was also studied in a recent experiment [31].In this work we address the impact of isospin dynamics on fusion barriers and cross-sections using the microscopic timedependent Hartree-Fock (TDHF) theory [32,33] together with the density-constrained TDHF (DC-TDHF) method for calculating fusion barriers [34]. In the TDHF approximation the many-body wavefunction is replaced by a single Slater determinant and this form is preserved at all times, implying that two-body correlations are neglected.…”
mentioning
confidence: 83%
“…Recent TDHF studies have been performed to investigate the charge equilibration in deep-inelastic collisions [46,48] and its impact on the interplay between fusion and transfer reactions [49][50][51][52][53][54]. Recent investigations have also shown that the one-body dissipation mechanisms included in TDHF were the most relevant to describe fully damped reactions such as quasi-fission [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, collective vibrations can appear built on any shape of the system during its path to fusion. In particular, the pre-equilibrium giant dipole resonance, which is excited in N/Z asymmetric collisions, has been studied in detail with modern TDHF codes [51][52][53]. It has been shown that the properties of the pre-equilibrium GDR could be used to infer the characteristics of the system on its path to fusion.…”
Section: Path To Fusion In Light Systemsmentioning
confidence: 99%
“…We then used this technique to investigate the impact of transfer on heavier systems where experimental signatures are not so clear [4,53]. The isovector reduction of the potential due to transfer channels depends naturally on the presence of positive Q−value transfer channels.…”
Section: (Isovector) Transfer Couplingsmentioning
confidence: 99%